PERAN ORANG TUA DALAM PENDIDIKAN DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA - Irma Rahayu; Asep Sahrul Gunawan (STKIP Subang, 2026)
The role of parents in the teaching and learning process is considered crucial in determining student learning success. This study aims to examine various forms of parental involvement and their impact on student success based on a review of existing literature. The method used is a literature study by identifying, collecting, and analyzing relevant scientific sources, namely using the keywords parental role, family support, and student learning outcomes. The results of the study indicate that parental involvement includes assisting students in learning at home, actively communicating with teachers, and participating in school activities. This study confirms that collaboration between families and teachers is a step towards creating an optimal learning environment, as well as being the basis for family-based education policies at the school and regional levels.